2023
DOI: 10.1039/d3tb00174a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a myocardial patch with mesenchymal stem cells and poly(CL-co-TOSUO)/collagen scaffolds for myocardial infarction repair by coaxial electrospinning

Yingwei Wang,
Zepei Fan,
Qi Li
et al.

Abstract: Stem cell cardiac patches have shown promising future for myocardium infarction (MI) therapy, but the characteristics of cardiac pulsation and tissue orientation lead to challenges in the design of cardiac...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…MSCs cultured on PCL fibers coated with PDA and PDA/RGD exhibited a more stretched and wellspread morphology. MSCs are considered to have good cell adhesion and a widespread distribution when they have spindle-like shapes or multipolar morphologies [ 27,38]. The polygonal cell morphology indicates that contact point formation between the cell and matrix was more stimulated [27], and we concluded that the PDA and PDA/RGD coatings enhanced the proliferation and viability of MSCs by promoting MSCs-to-PCL fibers surface interactions.…”
Section: Viability and Morphology Of Mscs Cultured On Pcl Fibersmentioning
confidence: 74%
See 1 more Smart Citation
“…MSCs cultured on PCL fibers coated with PDA and PDA/RGD exhibited a more stretched and wellspread morphology. MSCs are considered to have good cell adhesion and a widespread distribution when they have spindle-like shapes or multipolar morphologies [ 27,38]. The polygonal cell morphology indicates that contact point formation between the cell and matrix was more stimulated [27], and we concluded that the PDA and PDA/RGD coatings enhanced the proliferation and viability of MSCs by promoting MSCs-to-PCL fibers surface interactions.…”
Section: Viability and Morphology Of Mscs Cultured On Pcl Fibersmentioning
confidence: 74%
“…phenotypes of their surface markers, which are known to be positive for CD90 and CD73, and negative for CD34 [2,27]. These expression markers can also be used as standards for evaluating MSCs properties such as multilineage potential [27,38]. The expression levels of CD90 were 74.8% in pristine PCL fibers, 81.7% in PDA-coated PCL fibers, and 84.5% in PDA/RGD-coated PCL fibers.…”
Section: Viability and Morphology Of Mscs Cultured On Pcl Fibersmentioning
confidence: 99%
“…Besides the hybridization of multiple types of materials, heterogenous fibers (bioactive materials/synthetic polymers) and orchestrated fibers produced by advanced electrospinning techniques may achieve an identical objective by encouraging cellular functions and guiding cellular arrangement/migration, respectively. Despite the few reported studies, the structures composed of core–shell or Janus fibers, as well as aligned fibers, have been utilized as biofunctional scaffolds for tissue regeneration and repairs (e.g., blood vessel grafts [ 175 , 176 ], skin grafts [ 177 , 178 ], and cardiac patch [ 179 , 180 ]), demonstrating their potential to be advanced membranes in OOCs devices.…”
Section: Electrospinning For Precise Medicinementioning
confidence: 99%
“…14,17 In contrast, hydrogel patches reduce the risk of surgical invasiveness by utilizing polymeric materials capable of undergoing a sol–gel transition or incorporating memory-smart-responsive materials to load active substances into the hydrogel, thus promoting adhesion to and treatment of the infarcted area. 18,19 In comparison to hydrogel intramyocardial injections, the drug delivery of hydrogel patches necessitates traversing a dense myocardial layer, meeting increased wet adhesion requirements at the gel-solid interface, as well as possessing a higher level of surgical manipulation skills and experience. 18,20,21 Nevertheless, further clarification is required on the comparative effectiveness between the two therapeutic modalities: intramyocardial injections and hydrogel patches.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In comparison to hydrogel intramyocardial injections, the drug delivery of hydrogel patches necessitates traversing a dense myocardial layer, meeting increased wet adhesion requirements at the gel-solid interface, as well as possessing a higher level of surgical manipulation skills and experience. 18,20,21 Nevertheless, further clarification is required on the comparative effectiveness between the two therapeutic modalities: intramyocardial injections and hydrogel patches.…”
Section: Introductionmentioning
confidence: 99%